Historia ya elimu Tanzania : 1892 hadi sasa - Mbenna, F. X . 1930- Francis Xavier Mbenna (Dar es Salaam, Tanzania : Dar es Salaam University Press, 2009)
History of education in Tanzania from 1892 to present.
Includes bibliographical references
.
Keywords: Education -- Tanzania -- History